PENINGKATKAN KEMAMPUAN KOGNITIF SAINS ANAK USIA 5-6 TAHUN MELALUI MEDIA JERUK NIPIS DI RAUDHATUL ATHFAL AL MUNAWAROH CIKARANG BARAT BEKASI - Hidjanah Hidjanah; Nurhayati (STKIP Muhammadiyah Bogor, 2019)
This research aim to know the extent to which Citrus Media be able improve children cognitive science skills between 5-6 years old. The research was implemented at group B Raudhatul Athfal Al Munawaroh West Cikarang Bekasi.The methods on this research is Class Action Research (CAR). The research was implemented at the Raudhatul Athfal Al Munawaroh West Cikarang Bekasi. Techniques of data collection is done using observation instrument, field notes, and documentation conducted in every cycle. Result achieved show an improvement in children cognitive science skills between 5-6 years old after a given action as much as two cycles. Increase the ability of children can be seen from the data in each cycle result percentage, percentage of the result in pre cycle is 27%. Percentage of pre cycle low due to it has not given learning activity using citrus media. Percentage result in the first cycle occurs an increased as big as 58,75% this because it has been using citrus media, but has not yet maximally mastered. And percentage result on the second cycle become amount 86,25% due to the children have already been familiar with citrus media that is to capable of doing his own experiments and can conclude his experimental results. Implication of this research is election appropriate media by the society and school in teaching of cognitive science skill will be given optimal result in the ability of cognitive science early childhood. With cognitive sciencelearning for the next level will be easier and no more rigid learning (using LKA only) to early childhood in experimental / exploratory learning, especially in cognitive science teaching.